Presidents without Roots: Understanding the Peruvian Paradox. (September 2019) - Vergara, Alberto; Watanabe, Aaron
Peru's posttransition democracy presents a paradox: presidents have remained unpopular despite presiding over a period in which democratic institutions strengthened and the economy grew rapidly. O'Donnell's work on delegative democracy suggests that the Peruvian paradox results from weak vertical accountability. Since Peru's return to democracy, parties and civil society have been too weak to hold elected leaders accountable. Furthermore, presidents have faced opposition to reform from entrenched neoliberal technocrats. With no one holding them accountable and little capacity to govern, presidents have chosen to delegate decision-making authority to technocrats. Even when leaders have won office on reformist platforms, continuity has prevailed, and citizens have lost trust in their elected leaders. The origins of the Peruvian paradox and weak vertical accountability can be traced to the destruction of the institutional and organizational foundations of democracy in the 1990s under Alberto Fujimori's authoritarian regime. La democracia pos-transición en Perú presenta una paradoja: los presidentes siguen siendo impopulares a pesar de presidir un período en el que las instituciones democráticas se fortalecieron y la economía creció rápidamente. El trabajo de O'Donnell sobre la demo-cracia delegativa sugiere que la paradoja peruana resulta de una débil rendición de cuentas vertical. Desde el retorno de Perú a la democracia, los partidos y la sociedad civil han sido demasiado débiles para responsabilizar a los líderes electos. Además, los presidentes han enfrentado la oposición a la reforma de tecnócratas neoliberales atrincherados. Sin que nadie los responsabilice y con poca capacidad para gobernar, los presidentes han optado por delegar la autoridad en la toma de decisiones a los tecnócratas. Incluso cuando los líderes han sido eligidos en plataformas reformistas, la continuidad ha prevalecido y los ciudadanos han perdido la confianza en sus líderes electos. Los orígenes de la paradoja peruana y la débil rendición de cuentas vertical se remonta a la destrucción de los cimientos institucionales y organizativos de la democracia en la década de 1990 bajo el régimen autoritario de Alberto Fujimori.